Implementing Posters as Media to Teach Literacy in Blended Learning for Young Learners - Bayu Prayogi, I Gede; Padmadewi, Ni Nyoman; Juniarta, Putu Adi Krisna (Riviera Publishing, 2022)
This study aims to determine the effect of applying poster learning media which is integrated with the Blended learning method on increasing the literacy skills of young learners. This study used document analysis and statistical analysis of student scores in the experimental group using integrated learning with posters and the control group using conventional learning to compare literacy abilities between the two groups. all parties participated in this research activity, both teachers, students, and also researchers. In this study, there were two classes used, namely class V.B with a total of 30 students as the experimental group and class V.C with a total of 30 students as the control group. The results of this study indicate that there are significant differences in student scores in the Experiment group and the Control group. After carrying out the data analysis, the results of the t-test were 0.023, which is smaller than the standard alpha level (? = 0.05). it can be said that the application of posters integrated with the blended learning method has a significant effect